2019
DOI: 10.1186/s11671-019-3079-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Group Modification at the Edges of Carbon Quantum Dots on Fluorescent Emission

Abstract: We present a detailed investigation on the effect of functional group modulation at the edges of carbon quantum dots (CQDs) on the fluorescence from the CQDs. The CQDs attached by N, S, and P elements are synthesized via pyrolysis of a mixture of citric acid and NH 3 H 2 O, H 2 SO 4 , and H 3 PO 4 , respectively. Thus, part of –COOH at the edges of CQDs can be converted into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Begheri et al [ 42 ] have suggested that during the thermal treatment, along with CDs more carbonized carbon particles (MCCPs) may also be formed as a major by-product, which have quenching effects on the photoluminescence of the CDs. The full width at half maximum (FWHM) of the emission band was used to evaluate both the homogeneity of the CDs [ 43 ] and the synthesis reproducibility. So, the fluorescence emission band of GCDs with its maximum intensity at 418 nm presented a FWHM of (126 ± 4.5) nm.…”
Section: Resultsmentioning
confidence: 99%
“…Begheri et al [ 42 ] have suggested that during the thermal treatment, along with CDs more carbonized carbon particles (MCCPs) may also be formed as a major by-product, which have quenching effects on the photoluminescence of the CDs. The full width at half maximum (FWHM) of the emission band was used to evaluate both the homogeneity of the CDs [ 43 ] and the synthesis reproducibility. So, the fluorescence emission band of GCDs with its maximum intensity at 418 nm presented a FWHM of (126 ± 4.5) nm.…”
Section: Resultsmentioning
confidence: 99%
“…Poor size control [19,[37][38][39][40][41][42][43][44] Avoids use of strong acids or alkalis, cost effective, suitable for widely different carbon sources…”
Section: Methods Schematic Synthesis Advantages Disadvantages Referencementioning
confidence: 99%
“…(C) Emission curves for the as-synthesized GQDs in acid conditions zag perimeter after doping produced an increase in the absorbance accompanied of a red-shifting [31]. On the other hand, an increment in the number of carboxyl groups at the edges of GQDs produces an increase in the nonradiative recombination of the electronic transitions, thus, reducing the quantum yield efficiency [32]. Absorbance spectra of all GQD types (Figure 2B) showed a broad band in the range of 350-400 nm, being very intense for those with passivated surfaces.…”
Section: Preparation and Characterization Of Gqdsmentioning
confidence: 99%
“…Smaller sizes of the dots (a5-and o5-GQDs) after longer reaction time achieved blue-shifted emission bands [33]. Blue-shifting emission may be possibly due to -OH groups and free zigzag sites states as the major contribution while the greener emission may be attributed to the presence of mostly -COOH functional groups as occurred in o1-GQDs [32]. The trend regarding the PL intensity is as follows: a5-GQDs > a1-GQDs > o1-GQDs > o5-GQDs, which is related to the oxidation degree (more oxidation of the layers led to less intense PL intensity).…”
Section: Preparation and Characterization Of Gqdsmentioning
confidence: 99%